Dynamic Changes in Surface Damage Induced by High-Intensity Mining of Shallow, Thick Coal Seams in Gully Areas - Jianwei Li; Xintian Li; Changyou Liu; Xiangye Wu (Advances in Civil Engineering)
This study proposes a novel approach to study the mechanism of mining and dynamic changes in surface subsidence and geological hazard-prone regions caused by shallow, thick coal seam mining in gully areas. This approach combines field observation, three-dimensional modeling, numerical simulation, and theoretical analysis based on the conditions of the Chuancao Gedan coal mine. The in situ stress field of coalbeds is influenced by the gully terrain. Shear stress becomes concentrated on the surface, causing geological disasters such as landslides and collapse of gully slopes. High-intensity mining activities increase the concentration and are more likely to cause such geological disasters. The influence area and severity vary dynamically with the expansion of the excavation area. With the continuous expansion of coal seam mining, the amplification ratio η (the ratio of the maximum impact range of surface subsidence and the mined-out area) first increased to 3.35, then decreased, and finally reached a constant value of 2.1. The principle of road line selection is proposed based on an analysis of surface subsidence and gully slope stability on the goaf edge. The principle of subsection reinforcement of the gully slope under the dynamic influence of coal seam mining is also determined.